Practice and relevance of sports psychiatry in promoting athletes' mental health in Japan - Tatsuya Yamaguchi (Hogrefe AG, 2024)
Abstract: Introduction: This article outlines the important and varied role of sports psychiatrists in Japan and highlights the unique challenges and contributions of sports psychiatry to improving the mental health and performance of athletes. The report emphasizes the need for accurate assessment, diagnosis and treatment of mental health problems in athletes and recognizes the cultural stigmas and pressures specific to competitive sport in Japan. Methods: The paper first reviews the development of sports psychiatry with reference to the founding principles of the International Society for Sports Psychiatry and the Japan Association of Sports Psychiatry. It examines the integration of sport into psychiatric care and vice versa and indicates the value of research in the relationship between exercise and mental well-being. Results: This paper also explores the development of comprehensive diagnostic guidelines, the creation of tailored therapeutic approaches in clinical practice, the promotion of collaborative research to advance the field, and the educational development of psychological specialists. The role of sport psychiatrists in education and public awareness is examined, as well as the importance of destigmatizing mental illness in sport and improving mental health literacy among athletes and their support networks. Conclusion: Overall, this article describes the evolving and multifaceted role of sports psychiatrists in Japan, highlighting their crucial contributions to athlete care, research, education and public awareness. It advocates a flexible and adaptable approach to meeting the ever-changing demands of sports and upholding the mental health needs of athletes.